Development of an LC‐MS/MS‐based assay to determine artemitin in rat plasma and its application in a pharmacokinetic study. (29th August 2018) - Han, Xiaoli; He, Jinhua; Chen, Qinyue; Sun, Yali; Zhang, Xiulei; Gu, Zhengyi; Sha, Xianyi
Abstract: Artemitin, a significant flavonol compound existing in Laggera pterodonta (DC.) Benth., Artemisia rupestris L, etc., is the subject of attention by researchers owing to its pharmacological activities (such as antioxidative, anti‐inflammatory and antiviral). In this work, a highly sensitive and specific high‐performance liquid chromatography–electrospray ionization–tandem mass spectrometry (HPLC‐ESI‐MS/MS) assay combined with protein precipitation has been established and validated for determining artemitin concentration in rat plasma. Both artemitin and warfarin sodium (internal standard, IS) were separated on an Agela Venusil XBP Phenyl column through the isocratic elution mode of methanol–water containing 0.1% formic acid (80:20, v/v), at a flow rate of 0.4 mL/min. The MS/MS system was operated in a positive ion and ESI multiple reaction monitoring mode, and the multiple reaction monitoring transition was optimized as m / z 389.0 → 373.0 for artemitin and 309.2 → 163.0 for IS. The method showed good linearity in the range of 2.5–2000 ng/mL ( R 2 = 1.0000) and high sensitivity for artemitin with the lower limit of quantification of 2.5 ng/mL. The intra‐ and inter‐day accuracies were 97.4–100.9 and 93.4–100.3%, respectively. The intra‐ and inter‐day precisions were <4.8 and 6.5%, respectively. The extraction efficiency and absolute recovery were >66.5 and 71.3%, respectively. In addition, a good matrix effect of <9.5% was obtained. As a result, the method developed herein was successfully applied for the pharmacokinetic study of artemitin after an intravenous administration in rats.